Postcholecystectomy syndrome: a case report - Krishna Kumar, Dhakchinamoorthi; Pavitha P., Leena; Prukruthi, Ramachandran; Tabassum, Fathima; Bellja, J. B. Shalam; Madhumathi, Hanumakonda (International Journal of Scientific Reports, 2020)
The term postcholecystectomy syndrome (PCS) refers to varied signs and symptoms attributed to patients on cholecystectomy for the surgical management of symptomatic gallstone disease. This complication occurs as a result of a pathological condition of the gallbladder or attribution of several symptoms. PCS affects about 10-15% of the patients. The management and treatment of PCS associated symptoms are depending on the specific diagnosis and may include pharmacological or surgical management. In the present case, a 74-year-old man undergone for laparoscopic cholecystectomy admitted with complaints of loose stools for several times with other complications (anaemia, leucocytosis, neutrophilia, and also reported known case of trigeminal neuralgia). The present case report added insight information on PCS and its therapeutic management.